Industrial Discipline and Disciplinary Proceedings Mechanism in Industry in Bangladesh - Hasina, Nusrat; Islam, A. S. M. Zahidul (Global Disclosure of Economics and Business, 2015)
Industrial Law, though it has grown prolific in recent years, lacks in one vital aspect, that is, it has no clear and understandable disciplinary procedure. Disciplinary action can be taken by the employer against an employee committing any misconduct mentioned in the statutory law and punishment can be awarded as deemed suitable in the circumstances of the case after making an enquiry as may be necessary. But principles of disciplinary action is not laid down anywhere in any enactment or any other rules framed so far. The result is that each employer has his own idea of discipline and his own method of its enforcement. Since so uniform guidelines of discipline exist in industrial law, an employer even though he wishes to be fair to the delinquent employee, often commits procedural errors which is natural in the absence of such guiding rules. This paper aims to improve our understanding the gap between existing law and real scenario relating to industrial discipline and disciplinary proceedings mechanism in industry in Bangladesh. This lacuna has, however, been made good by judicial pronouncement dealing with every aspect of disciplinary events in the industry. A domestic enquiry is based mainly on the principles of natural justice and procedure laid down by various decisions of the Apex Court which now provide for guiding principles in disciplinary action in industrial concerns.JEL Classification Code: K3